2003
DOI: 10.1007/978-3-642-55566-4_23
|View full text |Cite
|
Sign up to set email alerts
|

The Minimal Number of Triangles Needed to Span a Polygon Embedded in ℝd

Abstract: Given a closed polygon P having n edges, embedded in R d , we give upper and lower bounds for the minimal number of triangles t needed to form a triangulated PL surface embedded in R d having P as its geometric boundary. More generally we obtain such bounds for a triangulated (locally flat) PL surface having P as its boundary which is immersed in R d and whose interior is disjoint from P . The most interesting case is dimension 3, where the polygon may be knotted. We use the Seifert surface construction to sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…For more studies of related problems, see works of Hass et al, e.g. [13,14,15,16]. The problem of having the least number of triangles to span a polygon embedded in R n is studied in [15].…”
Section: Minimal Area Vs Minimal Genus Vs Computational Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…For more studies of related problems, see works of Hass et al, e.g. [13,14,15,16]. The problem of having the least number of triangles to span a polygon embedded in R n is studied in [15].…”
Section: Minimal Area Vs Minimal Genus Vs Computational Complexitymentioning
confidence: 99%
“…[13,14,15,16]. The problem of having the least number of triangles to span a polygon embedded in R n is studied in [15]. It brings us to the context of finite element meshes, where we can also consider different mesh-dependent optimality criteria for cuts.…”
Section: Minimal Area Vs Minimal Genus Vs Computational Complexitymentioning
confidence: 99%
“…In the direction of PL combinatorial bounds, Hass and Lagarias [17] showed that there is a (qualitative) combinatorial analogue of the isoperimetric inequality (1) above in R 3 .…”
Section: Theorem 15mentioning
confidence: 99%
“…embedded polygons in R 3 . For piecewise linear curves, one can consider combinatorial analogues of isoperimetric inequalities, in which the "length" is replaced by the number of edges n in a polygon, and the "area" is the number of triangles in an embedded triangulated surface having the polygon as boundary, as in [17]. We establish the following PL analogue of Theorem 1.1 above.…”
Section: Introductionmentioning
confidence: 99%